2016
DOI: 10.2460/javma.248.4.405
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of thoracolumbar and lumbar intervertebral disk extrusions in English Cocker Spaniels

Abstract: OBJECTIVE To assess the anatomic distribution of thoracolumbar and lumbar intervertebral disk extrusions (IVDEs) in English Cocker Spaniels as compared with findings in Dachshunds and to characterize clinical findings in English Cocker Spaniels with thoracolumbar or lumbar IVDEs affecting various regions of the vertebral column. DESIGN Retrospective observational study. ANIMALS 81 English Cocker Spaniels and 81 Dachshunds with IVDEs. PROCEDURES Signalment, clinical signs, neurologic examination findings, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Canine lumbosacral disk disease is often associated with IVDP, but few reports have described IVDE of the L7-S1 disk in dogs. 12,22,23 As a result, detailed information on clinical signs, MRI findings, and postoperative outcome is scarce. In this study, we describe 13 dogs with surgically confirmed lumbosacral IVDE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Canine lumbosacral disk disease is often associated with IVDP, but few reports have described IVDE of the L7-S1 disk in dogs. 12,22,23 As a result, detailed information on clinical signs, MRI findings, and postoperative outcome is scarce. In this study, we describe 13 dogs with surgically confirmed lumbosacral IVDE.…”
Section: Discussionmentioning
confidence: 99%
“…Thickening of the spinal nerves and adhesions with surrounding tissues was also reported to complicate surgery in English Cocker Spaniels with caudal lumbar IVDE, including four with lumbosacral disease. 23 Subsequently, delaying diagnosis and surgical treatment was proposed to initiate this cascade of morphological changes. In this study, median time from onset to surgery was longer in dogs with changes secondary to inflammation than in those without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, IVDD is likely a polygenic disorder with many environmental influences. The pattern of IVDD incidence spans a variety of other breeds, there is wide variety in age at onset of clinical signs, and a number of environmental risk factors have been associated with IVDD, thus indicating a complex, multifactorial aetiology [10, 13, 1618]. …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Similar to previous reports the German shepherd dog was the most afected breed in this study. 1 8 11 2 5 Interestingly cocker spaniels, a breed reported to present with caudal lumbar disc herniation, 26 represented 8.8 per cent of this population while being sparsely represented in previous DLSS reports. 1 4 5 11 13-19 The majority of cases in this study underwent surgery following unsuccessful conservative treatment (91.1 per cent).…”
Section: Discussionmentioning
confidence: 98%